Variation in vertical stress in the Baram Basin, Brunei: tectonic and geomechanical implications - Tingay, Mark; Hillis, R.; Morley, C.; Swarbrick, R.; Okpere, E. (Elsevier, 2003)
The vertical or lithostatic stress is an important factor in tectonic and geomechanical studies and is commonly used in the prediction of pore pressures and fracture gradients. However, the vertical stress is not always calculated in situ and the approximation of 1.0 psi/ft (22.63 MPa/km) is often used for the vertical stress gradient. Vertical stress has been determined in 24 fields in the Baram Basin, Brunei, using density log and checkshot velocity survey data. The Baram Basin shows a variation in vertical stress gradient between 18.3 and 24.3 MPa/km at 1500 m depth below the surface. This variation has a significant effect on in situ stress related issues in field development such as wellbore stability and fracture stimulation. The variation is caused by a bulk rock density change of 2.48-2.07 g/cm3 from the hinterland of the delta to its front. Differential uplift and erosion of the delta hinterland and undercompaction associated with overpressure are the interpreted causes of the density and hence vertical stress variation.